The Use of Botulinum Toxin in the Treatment of Trigeminal Neuralgia (Fifth Cranial Nerve) - Marín Naranjo MQC, MSc, Rita María (Odovtos - International Journal of Dental Sciences, 2018)
The Trigeminal Neuralgia (TN) is described as neuropathic pain at the orofacial level, characterized by unbearable pain that can last from a few seconds to several minutes. The different treatments used for these patients are to numb the nerve, surgical, pharmacological, and the administration at extra and intraoral level of botulinum toxin, which is a neurotoxin produced in cultures of the bacterium Clostridium botulinum in a natural way; in the sporulation process are 7 subtypes being the subtype A the most used in neurological problems. The botulinum toxin acts as a neuromuscular blocker, by inhibiting the release of acetylcholine at the synaptic space, which is an important neurotransmitter to produce local muscle relaxation, and the patients report reductions in the frequency and intensity of pain with minimal side effects. The injection of botulinum toxin produces an effective pain reduction of neuropathic origin in the hyperalgesic tissue and is used as adjuvant therapy when oral medications do not give adequate control of pain. Over time it is expected to reduce the drugs as the patient tells that the pain has decreased or is being controlled. Patients are indicated the variation of time in which they can obtain relief of their pain. In patients with uncontrolled pain of the trigeminal nerve, the toxin is placed extraoral in the orofacial region with high effectiveness, but there is a lack of studies on the administration in the intraoral submucosal.